Fundamentals of entrepreneurship (ENT300) : F5's steamboat and grill / Munai Majing ... [et al.] - Majing, Munai; Penny, Divya; Kenny, Melvina Selvia; Nyuin, Suzie Sudan; Ding, Nancy Usun (2015)
F5's Steamboat and Grill is founded in the year of 2015 and is a special concept restaurant targeted to have demand in the steamboat restaurant in the near future. It is formed under the Business Registration Act 1956 (Amendment 1978) and Procedures of Business Registration 1957 where we form a partnership. Our steamboat restaurants located at Desa Ilmu F5's Steamboat and Grill with a concept "Treat Yourself and Enjoy Food" for customers to experience with variety of seafood, chicken and beef meat as a main dishes. Customers can take their time to enjoy all food which they want with only RM20 per entry.